Short Communication: Beta-adrenergic agonists alter oxidative phosphorylation in primary myoblasts. (1st August 2022) - Sieck, Renae L; Treffer, Leah K; Fuller, Anna M; Ponte Viana, Martonio; Khalimonchuk, Oleh; Schmidt, Ty B; Yates, Dustin T; Petersen, Jessica L
Abstract: Beta-adrenergic agonists (β-AA s) are widely used supplements in beef and pork production to improve feed efficiency and increase lean muscle mass, yet little is known about the molecular mechanism by which β-AAs achieve this outcome. Our objective was to identify the influence of ractopamine HCl and zilpaterol HCl on mitochondrial respiratory activity in muscle satellite cells isolated from crossbred beef steers ( N = 5), crossbred barrows ( N = 2), Yorkshire-cross gilts ( N = 3), and commercial weather lambs ( N = 5). Real-time measurements of oxygen consumption rates (OCR s) were recorded using extracellular flux analyses with a Seahorse XFe24 analyzer. After basal OCR measurements were recorded, zilpaterol HCl, ractopamine HCl, or no β-AA was injected into the assay plate in three technical replicates for each cell isolate. Then, oligomycin, carbonyl cyanide- p -trifluoromethoxyphenylhydrazone, and rotenone were injected into the assay plate sequentially, each inducing a different cellular state. This allowed for the measurement of OCR at these states and for the calculation of the following measures of mitochondrial function: basal respiration, non-mitochondrial respiration, maximal respiration, proton leak, adenosine triphosphate (ATP)-linked respiration, and spare respiratory capacity. Incubation of bovine cells with either zilpaterol HCl or ractopamine HCl increased maximal respiration ( P = 0.046) and spare respiratory capacity ( P = 0.035) compared with non-supplemented counterparts. No difference ( P > 0.05) was observed between zilpaterol HCl and ractopamine HCl for maximal respiration and spare respiratory capacity in bovine cell isolates. No measures of mitochondrial function (basal respiration, non-mitochondrial respiration, maximal respiration, proton leak, ATP-linked respiration, and spare respiratory capacity) were altered by β-AA treatment in ovine or porcine cells. These findings indicate that β-AAs in cattle may improve the efficiency of oxidative metabolism in muscle satellite cells by modifying mitochondrial respiratory activity. The lack of response by ovine and porcine cells to β-AA incubation also demonstrates differing physiological responses to β-AA across species, which helps to explain the variation in its effectiveness as a growth supplement. Lay Summary: Beta-adrenergic agonists (β-AA s) are supplemented to pigs and cattle to improve growth performance, carcass weight, and loin muscle area. Little is known about the mechanism taking place within individual cells by which β-AAs achieve this outcome. Previous work reported that β-AA supplementation improves the efficiency in which cells use glucose as an energy source and alters the expression of genes related to mitochondrial function, a key component of cellular energy production. To further our understanding of the impact of β-AA supplementation on these cellular functions, our objective was to identify the influence of two β-AAs used in livestock production, ractopamine HCl and zilpaterol HCl, on the mitochondrial respiratory activity of cells collected from the loin muscle and grown in culture. We isolated cells from cattle, pig, and sheep muscle and measured the oxygen consumption of the cells after treatment with ractopamine HCl, zilpaterol HCl, or with no supplement. We found that both ractopamine HCl and zilpaterol HCl enhance the efficiency of cellular energy production during a state of cellular stress in bovine muscle cells. There was no appreciable effect of the supplement on the energy production of pig or sheep cells. These data indicate that β-AA supplementation in cattle may increase the muscle cell energy production capacity compared with non-supplemented cells. This study also demonstrates that the efficiency of cell energy production is one plausible mechanism underlying species differences in the response to β-AA supplementation. Abstract : Beta-adrenergic agonist (β-AA ) supplementation may improve the efficiency of muscle satellite cells in part by modifying mitochondrial respiratory activity. Additionally, mitochondrial efficiency is one plausible mechanism underlying the differing physiological responses to β-AA across livestock species.